Suppression of TNF-alpha expression, inhibition of Th1 activity, and amelioration of collagen-induced arthritis by rolipram. - Ross, SE; Williams, R; Mason, L; Mauri, C; Marinova-Mutafchieva, L; Malfait, A; Maini, R; Feldmann, M (1997)
Rolipram is a type IV phosphodiesterase inhibitor that suppresses inflammation and TNF-alpha production. As anti-TNF-alpha therapy is effective in rheumatoid arthritis, we investigated the effect of rolipram on collagen-induced arthritis (CIA), a murine model of rheumatoid arthritis. Rolipram was administered after the onset of clinical arthritis at doses of 0.5, 3, 5, or 10 mg/kg twice daily, with a dose-dependent therapeutic effect on clinical severity and joint erosion. Immunohistochemical analysis of joints of rolipram-treated mice revealed 67% reduction in TNF-alpha-expressing cells compared with control arthritic mice. In vitro studies using bone marrow-derived macrophages confirmed that rolipram directly suppressed TNF-alpha and IL-12 production following stimulation with IFN-gamma and LPS. The effect of rolipram on T cell activity was studied by measuring Th1/Th2 cytokine production by collagen-stimulated draining lymph node cells from arthritic mice treated in vivo with rolipram. Rolipram reduced IFN-gamma production and increased IL-10, indicating that rolipram down-regulated the ongoing Th1 response to type II collagen. Finally, the effect on CIA of combination therapy was studied using rolipram plus either anti-TNF-alpha or anti-CD4 mAbs. Rolipram plus anti-TNF-alpha was not therapeutically additive, whereas rolipram plus anti-CD4 mAb was clearly additive. This result indicates that the therapeutic effects of rolipram overlap with TNF-alpha blockade, but are complementary to anti-CD4 treatment. It is therefore proposed that a major mechanism of action of rolipram in CIA is suppression of TNF-alpha activity. These findings suggest that type IV phosphodiesterase inhibitors may be effective in pathologic conditions, such as RA, with overexpression of TNF-alpha.